An Analysis of Material Completeness in English Textbook â€œWhen English Rings A Bellâ€ of Junior High School - Dinata, Ridho Praja; Basid, Muhammad Adji (Universitas Batanghari Jambi, 2022)
This research purposed to analyzed the material completenss in the English textbook entitled â€œWhen English Rings a Bellâ€ by Ministry of Education and Culture. The material completeness that were expected to found were a short interpersonal text, a short transactional text and a short functional text. This researchused qualitative research design and descriptive qualitative approach to analyzed the English textbook. Specifically, this researchused checklist in gathering the data. The data were gathered by reading the English textbok throughly to identify and classify the material completeness that can be found. This researchanalyzed the data by the results of the research. The result showed that â€œWhen English Rings a Bellâ€ textbook that published by the ministry of education and culture was provides and presents the material completeness, there were: 1) A short interpersonal text, providing introducing self and others namely introducing self, greeting, leave taking, thangking and aologizing. 2) A short transactional text, such as: telling about daily activity, asking and giving direction, asking and giving information (related to the qualities of people, animals and things, in order to identify, to criticize or to praise them and related to actions/functions of people, animals and things in order to identify, to criticize or to praise them). And 3) A short functional text, this English textbook provides a short functional text, namely a descriptive text. The result of this research showed that â€œWhen English Rings a Bellâ€ textbook fulfill and provide the material completeness aspect.